2015
DOI: 10.1007/s00701-015-2478-5
|View full text |Cite
|
Sign up to set email alerts
|

Emergent cervical surgical embolectomy for extracranial internal carotid artery occlusion

Abstract: Cervical surgical embolectomy for acute extracranial ICA occlusion resulted in a high complete recanalization rate with an acceptable safety profile. A possible association between severe cardiac illness and huge embolus occluding proximal large artery was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…34 Our data, with a 58% favorable outcome, are in the middle of the reported results. Mortality rates showed also a considerable variability between studies [6%, 36 21%, 12 9%, 30 0% 5,31,34 ] and 0% in the current study. Mortality, in particular, seems low when compared to the general use of t-PA (*15%-25% mortality).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…34 Our data, with a 58% favorable outcome, are in the middle of the reported results. Mortality rates showed also a considerable variability between studies [6%, 36 21%, 12 9%, 30 0% 5,31,34 ] and 0% in the current study. Mortality, in particular, seems low when compared to the general use of t-PA (*15%-25% mortality).…”
Section: Discussionmentioning
confidence: 48%
“…However, endovascular treatment allows for the treatment of intracranial vessel occlusions. Following surgery, reports of good clinical outcomes varied considerably, with rates of 23%, 36 38%, 12 63.6%, 30 71.4%, 31 75%, 5 and up to 83.3%. 34 Our data, with a 58% favorable outcome, are in the middle of the reported results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that up to 8% of AIS may be due to ICA stenosis, 7 whereas acute cardiogenic emboli resulting in extracranial ICA occlusions account for only 0.3% of strokes. 16 Likewise, we were not able to determine the timing of angioplasty or stenting required to traverse the ICA and gain intracranial access given the retrospective nature of the study. Finally, it is difficult to discern any potential effect that ACA infarctions may have had on this small study population.…”
Section: Limitationsmentioning
confidence: 99%